Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Produktivitas Karyawan Pengadilan Agama Jakarta Barat - Nopianti, Sari; Rini, Ratih Setyo (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the influence of the work environment and discipline on employe productivity at the West Jakarta Religious Court. A total of 50 respondents were involved in this study, using a saturated sampling technique, meaning the entire population was used as the sample. Data were obtained thru the distribution of questionnaires and analyzed using multiple linear regression with the help of SPSS version 25 software. The results of the partial test (t-test) indicate that the work environment variable has a significant influence on productivity, with a significance value of 0.000 (< 0.05) and a calculated t-value of 4.850 (> t-table 2.010). Similarly, the work discipline variable also shows a significant influence with a significance value of 0.046 and a calculated t-value of 2.046. Furthermore, the results of the simultaneous test (F-test) indicate that both independent variables together have a significant effect on productivity, with an F-value of 61.932 (> F-table 4.46) and a significance value of 0.000. Thus, it can be concluded that the work environment and work discipline, both individually and simultaneously, positively and significantly contribute to the improvement of employe productivity at the West Jakarta Religious Court.